Marlborough Graphics. (London : Marlborough Fine Art Ltd., 1967)
Armitage, Kenneth ; Auerbach, Frank ; Bill, Max ; Burri, Alberto ; Chadwick, Lynn ; Dorazio, Piero ; Erni, Hans ; Gottlieb, Adolph ; Guston, Philip ; Herman, Josef ; House, Gordon ; Kitaj, R.B. ; Kokoschka, Oskar ; Lanceley, Colin ; Lin, Richard ; Lucebert ; Maier-Denninghoff, Brigitte ; Marca-Relli, Conrad ; Moore, Henry ; Nicholson, Ben ; Nolan, Sidney ; Pasmore, Victor ; Pepper, Beverly ; Piper, John ; Pomodoro, Gio ; Rebeyrolle, Paul ; Richards, Ceri ; Stroud, Peter ; Sutherland, Graham ; Tilson, Joe ; Turcato, Giulio ; Whiteley, Brett ; Wotruba, Fritz
geboortedata per kunstenaar
Engels
Marlborough Graphics, Marlborough Fine Art Ltd., London, 12.1976 - 15.01.1968
boek